L’extension du people dans la presse quotidienne - Gilles Labarthe (Communication)
Celebrity news in French Switzerland’s daily and weekly press is a relatively recent, and growing, development. How does this « new » subject matter affect the motivations, working conditions, and deontology of journalists ? Based on ten interviews conducted in 2007, this article offers some insight into celebrity news. The main argument put forth by the interviewees to justify this growing presence is mainly economic.